A convenient one-pot synthesis of: N -substituted amidoximes and their application toward 1,2,4-oxadiazol-5-ones - Wong Phakhodee (2018)
© 2018 The Royal Society of Chemistry. The first direct one-pot approach for the synthesis of N-substituted amidoximes from secondary amides or the intermediate amides has been developed. Through the Ph3P-I2-mediated dehydrative condensation, a variety of N-aryl and N-alkyl amidoximes (R1(CNOH)NHR2, where R1 or R2 = aryl, alkyl, or benzyl) were readily afforded under mild conditions and short reaction times. The synthetic application of the obtained amidoximes has also been demonstrated through the formation of 1,2,4-oxadiazolones via base-mediated carbonylative cyclization with 1,1′-carbonyldiimidazole.